Cardiac Biomarkers in Cryptosporidium-Induced Diarrhea: Evaluating Sepsis-Associated Myocardial Dysfunction in Calves - Balıkçı, C; Gülersoy, E; Paksoy, N; Şahan, A; Günal, İ (Journal of the Hellenic Veterinary Medical Society, 2026)
The aim was to investigate the relationship between cardiovascular damage and sepsis in calves infected with Cryptosporidium spp. and to evaluate the efficacies of certain biomarkers. 21 calves were selected from 133 calves under the inclusion/exclusion criteria. Diarrheic calves with (n=7) and without sepsis (n=7) all affected by Cryptosporidium spp., and clinically healthy calves (n=7) were studied. The diagnostic efficacies of NT-proBNP and cTnI concentrations were evaluated across three groups. cTnI concentration exhibited significant differences among all the groups (p<0.001), with the highest level observed in the Sepsis group (256.13±88.23 pg/mL). The serum NT-proBNP concentration was highest in the sepsis group (162.12 ± 117.52 pg/mL). A statistically significant difference was observed between the sepsis and healthy groups (25.58 ± 13.24 pg/mL), as well as between the non-sepsis (112.39 ± 54.99 pg/mL) and healthy groups. Cardiovascular disorders may occur in neonatal diarrhea caused by Cryptosporidium spp., even without sepsis. When treating calf diarrhea caused by Cryptosporidium spp., it is crucial to consider cardiac involvement during prognosis evaluation and treatment planning.